Is more always better? An S-shaped impact of gamification feature richness on exercise adherence intention - Sun, Yi; Dong, Hongchi; Jiang, Wenyi (Frontiers in Psychology, 2025)
Gamification is widely used to promote exercise adherence, yet “more features” do not always strengthen intention to sustain exercise plans. This study theorized and tested a curvilinear–specifically S-shaped–association between gamification feature richness and exercise adherence intention. Using polynomial modeling and slope analysis, we delineated engagement and overload zones across the observed feature-richness range. The results supported the S-shaped pattern: intention increased from low to moderate richness but weakened when feature sets became excessive. Digital exercise self-efficacy did not support the hypothesized inattention zone, but it amplified gains in the engagement zone and attenuated losses in the overload zone. These findings suggest that gamification yields diminishing and negative returns beyond a “right-sized” set of features, and that designers and practitioners should avoid feature bloat while providing adaptive controls that allow users to streamline secondary mechanics.